Getting to Know the Educator's Requirements for Teachers in Efforts to Achieve the Goals of Islamic Education - Samuji, Samuji (Jurnal Paradigma, 2021)
n general, educators are people who have the responsibility to educate. Meanwhile, in particular, educators in the perspective of Islamic education are people who are responsible for the development of students by striving for the development of all potential students, both affective, cognitive, and psychomotor potential in accordance with the values of Islamic teachings. The purpose of Islamic education is to achieve a balance of human personality growth. As a whole and in a balanced manner which is carried out through training of the soul, mind, rational human self, feelings and senses, therefore, education should include the development of all aspects of the nature of students, spiritual, intellectual, imaginative, physical, scientific and linguistic aspects, both in a way. individually and collectively, and encourage all these aspects to develop towards goodness and perfection. Therefore, the ultimate goal of Islamic education falls within the same line as that mission, which is to form human abilities and talents in order to be able to create prosperity and happiness that is full of Allah's grace and blessings in all corners of this universe.